The experience of first-time, multi-pregnant mothers and nursing in newborn care from culture and belief (Cuidado y Ocupación Humana, 2024)
Introduction: From nursing it is essential to know how much newborn care has changed over the years and how it is provided from different cultural origins, emphasizing the experience as a first-time or multi-pregnant mother and the way in which they have been guided. in the first days of life. Objective: To analyze the experience of first-time pregnant mothers, multi-pregnant mothers and nursing mothers in the care of the newborn from culture and belief in the year 2023-2024. Method: A qualitative-ethnographic investigation was developed, using two semi-structured interviews prepared by the author. Results: It was demonstrated that there is a relationship between the company that the mothers have and the perception they have in the postpartum period, as well as the variety of omens and similarities present in the mothers. On the nursing side, there is a relationship between work experience and the perception of the evolution of care. Conclusions: The evolution of the care provided by nursing is evident, given the constant medical-scientific training and the knowledge and experiences of mothers regarding the care of the newborn is variable, being specifically adopted from the social environment and creating a deep roots. from the same.
Keywords: Beliefs; traditions; care; newborn; primigravidas; multipregnant